Seedling fate across different habitats: the effects of herbivory and soil fertility - Fleury, Marina [UNESP]; Silla, Fernando; Rodrigues, Ricardo Ribeiro; Couto, Hilton Thadeu Zarate do; Galetti, Mauro [UNESP] (Elsevier B.V., 2015)
The impact of extinction of predators and subsequent herbivore release on ecosystem functioning has been well studied in temperate ecosystems, yet we have very little information on threatened tropical rainforests. Herbivore overbrowsing can have profound effects on ecosystem processes through overconsumption or by altering organic inputs of leaves and roots as well as changing soil physical and chemical properties. We evaluated the fate of transplanted seedlings of four tropical tree species and nutrient availability in open control plots and enclosed plots that permitted free access by insects and excluded vertebrates and collected soil samples in old-fields, early secondary forests and old-growth forests. Seedling damage predominantly occurred in the dry season and produced an overall seedling mortality of 72%, with values of 43% and 86% in the plots that prohibited and permitted vertebrate access, respectively. Except for Myrsine coriacea in the old-fields and Syagrus romanzoffiana in the early secondary forest, seedlings suffered greater rates of damage and mortality in the open plots, showing that the aboveground large herbivores, such as capybaras (Hydrochoerus hydrochaeris), might prevent or at least delay plant recruitment in tropical areas supporting elevated densities. However, delayed deaths from disease by soil fertility-related factors were observed in late summer in the old-field seedlings, suggesting that previous activities in these areas had led to profound changes in the soil properties. Herbivores may have important consequences for tropical forest regeneration, as overconsumption may slow down nutrient cycling, promote cascading bottom-up effects on consumers, and ultimately lead to ecological meltdown. These consequences provide insight into the ecological effects of faunal change on human-altered tropical habitats.
Keywords: Atlantic forest; Capybaras; Cascading effects; Herbivores; Seedling limitation